Weighty Conversations: Caregivers', Children's, and Clinicians' Perspectives and Experiences of Discussing Weight‐Related Topics in Healthcare Consultations. Issue 11 (1st October 2018) - Jachyra, Patrick; Anagnostou, Evdokia; Knibbe, Tara Joy; Petta, Catharine; Cosgrove, Susan; Chen, Lorry; Capano, Lucia; Moltisanti, Lorena; McPherson, Amy C.
Abstract : Children with autism spectrum disorder (ASD) are at a higher risk of having obesity than their typically developing peers. Although it has been recommended that health care providers (HCPs) speak to caregivers and children about the risk of higher weights, no research has examined how HCPs communicate weight‐related information. Furthermore, there is a dearth of evidence regarding how to approach and deliver optimal weight‐related discussions among children with ASD and their caregivers. Given these knowledge gaps, 21 in‐depth interviews were conducted with children with ASD, their caregivers, and HCPs. Using a qualitative analytic approach, data from interviews were analyzed thematically. Results suggest that HCPs at times projected weight stigma during clinical encounters, which did not motivate children and caregivers to work toward work loss or wellness. HCPs also described reticence in engaging families in weight‐related conversations due to limited training, and lack of clinical tools to guide these conversations. All stakeholders identified a need to work together to establish a therapeutic partnership to discuss weight‐related issues without blame or shame. The combination of strength‐based communication approaches, establishing a strong therapeutic partnership, and development of clinical tools facilitating weight‐related discussions for HCPs outlined in this article are potential vehicles to foster successful weight‐related discussions while promoting lifelong wellness. Autism Research 2018, 11: 1500–1510 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Children with autism spectrum disorder (ASD) are at a higher risk of having obesity. Yet, it is unknown how healthcare providers (HCPs) should deliver weight‐related information. Findings suggest children and caregivers experienced weight stigma and were uncomfortable discussing weight‐related issues. HCPs identified that they did not have sufficient training, and did not feel confident identifying/addressing weight issues. Tools are needed to facilitate weight‐related discussions among children, caregivers and HCPs.